2022
DOI: 10.1186/s13256-022-03546-w
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal obstruction due to jejunocolic congenital band in a 12-year-old child: a case report

Abstract: Background A congenital band is an uncommon abnormality that can be found anywhere along the gastrointestinal tract. Intestinal obstruction caused by an anomalous congenital band is very rare in children. To the best of our knowledge, no cases of congenital bands extending from the descending colon to the jejunum have been reported in the English literature Case presentation Herein, we present the case of a 12-year-old Syrian patient with intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Wu et al recently reported that laparoscopy in the diagnosis and treatment of a congenital band may be safe and feasible. 3,[12][13][14] The treatment consists of resecting the band and if necessary, resecting a necrotic small bowel loop. [15][16][17] By reporting this case, we emphasize the importance of considering CPBs in the differential diagnosis of bowel obstruction, particularly when patients lack typical risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wu et al recently reported that laparoscopy in the diagnosis and treatment of a congenital band may be safe and feasible. 3,[12][13][14] The treatment consists of resecting the band and if necessary, resecting a necrotic small bowel loop. [15][16][17] By reporting this case, we emphasize the importance of considering CPBs in the differential diagnosis of bowel obstruction, particularly when patients lack typical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…recently reported that laparoscopy in the diagnosis and treatment of a congenital band may be safe and feasible. 3 , 12 , 13 , 14 The treatment consists of resecting the band and if necessary, resecting a necrotic small bowel loop. 15 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Laparotomy has traditionally been recommended, but with the advent of minimally invasive surgery, laparoscopy has been proposed as an alternative. Wu et al recently reported that laparoscopy in the diagnosis and treatment of a congenital band may be safe and feasible [3]. The treatment consists of resecting the band and if necessary, resecting a necrotic small bowel loop.…”
Section: Discussionmentioning
confidence: 99%